An Elliptic Garnier System from Interpolation - Yamada, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
Considering a certain interpolation problem, we derive a series of elliptic difference isomonodromic systems together with their Lax forms. These systems give a multivariate extension of the elliptic Painlevé equation.